Experience of using vascularized bone grafts to treat nonunion fractures and limb bone defects - A. V. Nevedrov; E. Yu. Shibayev; V. O. Kalenskiy; N. N. Zadneprovskiy; V. B. Shishkin; F. A. Sharifullin; O. A. Tsoy; M. P. Lazarev; P. A. Ivanov; A. L. Rybinskaya (Трансплантология (Москва), 2019)
Background. Vascular bone graft transposition is the one of most effective method of nonunion fracture and bone defect treatment. However, the use of this technique is associated with some difficulties. One is the adjustment of recipient bed size and the graft. The other is the difficulty to reconstruct the alignment and length of bone. A promising method of preparing for the vascular bone graft transposition is virtual three-dimensional planning based on computed tomography data and three-dimensional printing templates.The aim was to summarize our experience in the treatment of bone nonunion and defects with vascular bone autografts using tree-dimensional virtual planning and printing.Material and methods. We analyzed the treatment process and outcomes of 4 patients with limb bone nonunion and 6 patients with bone defects. In all cases, we used vascular bone grafts. Internal fixation of grafts was used in 7 cases, external fixation was used in 3 cases. At preparation stage in 4 cases, we used tree-dimensional virtual surgery planning and printing templates.Results. One case was diagnosed with bone graft necrosis caused by venous thrombosis. Consolidation was achieved in all patients; a late consolidation was observed in 2 cases. Hematoma in donor area was seen in 2 patients. When using three-dimensional virtual planning and tree-dimensional printing templates, the operation time was decreased by 1 hour 5 minutes. We identified two cases of poor reposition in the group without virtual planning. No poor reposition was observed in the cases where tree-dimensional planning was used.Conclusion. Vascularized bone grafts provide an effective method to treat bone defects and nonunion. But the planning of graft and recipient site sizes is associated with certain difficulties. Our preliminary results have shown that virtual three-dimensional planning and printing allow improving the precision of the surgical procedure and decreasing operative time.